Growth and Income Distribution Inequalities in Sub-Saharan Africa: A Dynamic Model Approach - (:unkn) unknown (My University, 2021)
The objective of this paper is to study the link between the distribution of income and the economic growth using the data of sub-Saharan Africa during the period 1980-2015. The study was carried out by using a model of Quasi-maximum of likelihood for the estimations. This method is particularly adequate for estimates in panel where temporal dimension is small. The results, which rise from this study and start from the estimated models of Solow, show that inequalities have a positive effect on the economic growth. This effect varies from 0.70 point with 0.79 point. The mean number of years of schooling affects the growth of the GDP negatively. These results are stable even if we distinguish the human capital of male from the female one. It is also observed that in the model of Solow without human capital, the inequalities of incomes are not significant and can explain anymore in the economic growth.
Keywords: African Research